Lack of Information on Intangible Assets in the Financial Statements and a Way to Manage It - Ya. I. Ustinova (Учёт. Анализ. Аудит, 2020)
The article is devoted to the study of localization of the lack of information on intangible assets in traditional financial statements and the analysis of possible ways to manage it. The methodological framework of the research includes methods of comparative, logical analysis, typology and grouping, induction and deduction. The research resulted in ways and means of disclosing the external manifestations of this type of information gap in the reporting and their negative consequences. It also analyses the options for filling in this gap, first of all, by means of the report on intangible assets that complements the structure and contents of traditional statements, and its comparison with the information requests of the company’s stakeholders. The conclusion about the need to revise the concept of preparing and disclosing information about the company’s intangible assets in the financial statements is substantiated. The research can be used in developing the concept of accounting for intangible assets, which can ensure that the gap between the content of financial statements and the information needs of users is bridged.